Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/bjd.21665
|View full text |Cite
|
Sign up to set email alerts
|

Application of an infrared thermography-based model to detect pressure injuries: a prospective cohort study

Abstract: Background It is challenging to detect pressure injuries at an early stage of their development. Objectives To assess the ability of an infrared thermography (IRT)‐based model, constructed using a convolution neural network, to reliably detect pressure injuries. Methods A prospective cohort study compared validity in patients with pressure injury (n = 58) and without pressure injury (n = 205) using different methods. Each patient was followed up for 10 days. Results The optimal cut‐off values of the IRT‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…To detect the source of heterogeneity that affects the pooled effect size of association between hypertension and PU, subgroup analyses were performed on patient source, research design and primary disease (Table 2 ). In the subgroup analysis of patient source, the meta‐analysis results indicated no significant association between hypertension and PU in Asia group (OR = 1.12, 95% CI = 0.83–1.50, I 2 = 63%, p = 0.46) 11 , 12 , 17 , 20 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 and Non‐Asia group (OR = 1.20, 95% CI = 0.75–1.94, I 2 = 88%, p = 0.45). 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To detect the source of heterogeneity that affects the pooled effect size of association between hypertension and PU, subgroup analyses were performed on patient source, research design and primary disease (Table 2 ). In the subgroup analysis of patient source, the meta‐analysis results indicated no significant association between hypertension and PU in Asia group (OR = 1.12, 95% CI = 0.83–1.50, I 2 = 63%, p = 0.46) 11 , 12 , 17 , 20 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 and Non‐Asia group (OR = 1.20, 95% CI = 0.75–1.94, I 2 = 88%, p = 0.45). 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49).…”
Section: Resultsmentioning
confidence: 97%
“…In the subgroup analysis of patient source, the meta‐analysis results indicated no significant association between hypertension and PU in Asia group (OR = 1.12, 95% CI = 0.83–1.50, I 2 = 63%, p = 0.46) 11 , 12 , 17 , 20 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 and Non‐Asia group (OR = 1.20, 95% CI = 0.75–1.94, I 2 = 88%, p = 0.45). 10 , 18 , 19 , 21 , 23 , 26 In the subgroup analysis of study design, the results also showed no significant association between hypertension and PU in cohort study (OR = 1.16, 95% CI = 0.84–1.61, I 2 = 63%, p = 0.36) 10 , 11 , 17 , 21 , 22 , 27 , 28 , 31 , 32 and case–control study (OR = 1.14, 95% CI = 0.79–1.64, I 2 = 82%, p = 0.49). 12 , 18 , 19 , 20 , 23 , 24 , 25 , 26 , 29 , 30 Due to the primary disease difference, subgroup analysis was performed based on primary disease, and the results showed that there was a significant association between hypertension and PU in COVID‐19 patients(OR = 1.73, 95% CI = 1.35–2.22, I 2 = 0%, p < 0.0001), 10 , 21 , 26 whereas no association was found in str...…”
Section: Resultsmentioning
confidence: 97%
“…Trifarotene was developed as a fourth-generation topical retinoid, 20 years after the third-generation retinoid adapalene, 3 and clascoterone was approved by the US Food and Drug Administration as a topical androgen receptor inhibitor for acne in patients 12 years and older, in 2020. 4 On the other hand, high-quality, evidence-based results for acne treatments can be provided by randomized, double-blind, controlled trials with adequate sample size and reporting of efficacy, safety and tolerability core outcomes, as with the study of Picardo et al A considerable part of acne clinical research is limited by the lack of randomization, which may result in bias, or the lack of a control arm, which is necessary to demonstrate efficacy considering the fluctuating nature of acne. In turn, the design of new antiacne agents is only possible by building on previous laboratory research into key players in the pathophysiology of acne.…”
mentioning
confidence: 99%
“…The prospective cohort study reported by Jiang and coauthors in this issue of the BJD utilizes a handheld noncontact infrared thermal imaging device that may meet this need. 4 A recent systematic review evaluated the evidence to support the use of bedside technologies in the early detection of PIs. Of the five modalities identified (ultrasound, thermography, subepidermal moisture measurement, reflectance spectrometry and laser Doppler), subepidermal moisture had the most consistent findings.…”
mentioning
confidence: 99%
“…A simple, inexpensive and easy‐to‐use device to detect PIs early, before an open and deep wound is inevitable, would be extremely beneficial. The prospective cohort study reported by Jiang and coauthors in this issue of the BJD utilizes a handheld noncontact infrared thermal imaging device that may meet this need 4 …”
mentioning
confidence: 99%